1994
DOI: 10.3354/meps112143
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient depletion and particulate matter near the iceedge in the Weddell Sea

Abstract: The region between Elephant Island and the South Orkney Islands (53.5" S, 46.5" W) was occupied by Winter Weddell Sea water and a t h c k layer of summer and surface modified Weddell Water. High correlations between nutrients (nitrate, total inorganic carbon, silicate) and oxygen with salinity were found in the upper 150 m near the ice-edge. Nutrient depletion was calculated and correlated with the melting ice processes. When 1 m of ice melts, the average amount of total carbonate and nutrients removed is equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The slope of equation 2 is lower than the Redfield ratio and similar to that found in Antarctic waters (Copin-Montégut and Copin-Montégut, 1983;Pérez et al, 1994).…”
Section: Organic Matter In the Upper Mixed Layer The Excess Docsupporting
confidence: 82%
“…The slope of equation 2 is lower than the Redfield ratio and similar to that found in Antarctic waters (Copin-Montégut and Copin-Montégut, 1983;Pérez et al, 1994).…”
Section: Organic Matter In the Upper Mixed Layer The Excess Docsupporting
confidence: 82%
“…This is a situation similar to those at the ice-edge during the ice melting season. Ice-edge blooms are closely related to the water stratification, and the blooms are seeded from ice algae, which are released from sea ice with ice meltwater (Smith & Nelson 1985, Niebauer et al 1990, Pérez et al 1994, Jin et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…There are clear relationships in spring and summer between the physical regime and biological productivity at the ice-edge at the seasonal timescale (Smith & Nelson 1985, Niebauer et al 1990, Pérez et al 1994, Jin et al 2007. These studies showed that water stratification due to the supply of freshwater to the surface advances the ice-edge bloom that is seeded from ice algae in the meltwater supply.…”
Section: Introductionmentioning
confidence: 98%
“…The concentrations of chlorophyll a ranged from 11.3 to 28.1 in ST1 and from 8.4 to 16.3 µg L −1 in ST4. Possible correlation between PON and chlorophyll a indicated that PON was originated from plankton [25]. Concentrations of chlorophyll a fluctuated seasonally with the high concentration in April 2001 and with the relatively low concentration at other times.…”
Section: Water Qualitymentioning
confidence: 98%